Reproductive outcomes in fresh transfer cycles and antagonists with premature luteinizing and/or progesterone surge: a single center retrospective cohort study - Wei, Chun-Xiao; Zhang, Jian-Wei; Xiang, Shan; Lian, Fang (Frontiers in Endocrinology, 2024)
The optimal outcome of assisted reproductive technology is a successful live birth after fresh embryo transfer. However, the success pregnancy rate of fresh embryo transfer cycle in antagonist protocol is lower than that observed in other protocols. Despite the use of antagonists (GnRH-ant), the incidence of luteinizing hormone surge and elevated progesterone levels remain at approximately 5%-38% [1; 2; 3]. Progesterone is widely recognized to exert adverse effects on fresh embryo transfer outcomes. This study aimed to investigate the impact of luteinizing hormone surge and progesterone levels on live birth rate following fresh embryo transfer and explore appropriate progesterone thresholds to enhance pregnancy outcomes.Methods: This retrospective cohort study included a total of 1,177 antagonist protocol cycles with fresh embryo transfer. The patients were divided into four groups based on the presence of premature LH surge and progesterone level on trigger day＞1.5ng/ml. Then, the relationship between the variables and the pregnancy outcome was analyzed and compared in each group.The transient rise of luteinizing hormone did not impact pregnancy outcomes (P=0.345; P=0.3; P=0.787), in contrast to progesterone levels on the day of hHCG administration (P=0.047*; P=0.015*; P=0.021*). In cases with luteinizing hormone surge, elevated progesterone levels were correlated with higher antral follicle count (AFC), and as progesterone levels increased, a greater quantity of oocytes and embryos were obtained.However, there was no statistically significant difference in pregnancy outcomes. In cases without luteinizing hormone surge, elevated progesterone levels led to significantly poorer pregnancy outcomes. Furthermore, the curve-fitting and threshold-effect analysis revealed a notable decline in live birth rates when progesterone exceeded or equaled 1.10ng/ml (OR, 0.25; 95% CI, 0.09-0.66; P = 0.005*).The GnRH-ant antagonist dosage addition should be carefully selected in flexible antagonist protocols. The presence of elevated progesterone levels may be associated with improved embryo quality when luteinizing hormone surge occurred. In the absence of a luteinizing hormone surge, progesterone levels showed a larger impact on the pregnancy outcome, and fresh embryo transfer should not be performed if the progesterone level on the day of hHCG administration is higher than 1.10ng/ml.